If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 12y = -16 Solving 7x + 12y = -16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12y' to each side of the equation. 7x + 12y + -12y = -16 + -12y Combine like terms: 12y + -12y = 0 7x + 0 = -16 + -12y 7x = -16 + -12y Divide each side by '7'. x = -2.285714286 + -1.714285714y Simplifying x = -2.285714286 + -1.714285714y
| 9u-47=2u-4 | | x-3(x+1)=6y-5x | | x^4+4x^2-7=0 | | 1=18+a | | (x+3)(x+5)(x-7)(x-9)=1792 | | 3x=f(w+5)+8 | | (x+3)(x+5)(x-7)(x-9)=0 | | f(w+5)=3x-8 | | 3x-4-5x=-3x-2 | | 36=14x-13x+8 | | 8-x=2x+8 | | 15x=-60 | | 7x-1=7(x+6) | | 2x-y-z=5 | | 0.01(x+6)-0.06=0.01(7x+6) | | 4(5y+4)=9(y+8) | | 4x^4+4x^2+4=0 | | 17x-7y=11 | | 8x+25=3x+50 | | r+19=25 | | 5=-2-x | | 10x+24=4x+126 | | a+2b=180 | | 3.9x=2.2x+10.2 | | 3.5x-20=2.4x+12 | | 254-7x=38x+24 | | x-21=-9 | | y/5+3/8=y/8-3/8 | | 19+k=-2 | | 4n/3-2/7=50/21 | | -2x-4x+13=-4-5x-10 | | b-18=-6 |